THE SUBJECT ELEMENT IN CONTRACT AND OBLIGATION: A COMPARATIVE ANALYTICAL LEGAL STUDY - Abdullah Mukhlif Tarrad (Indonesia Private Law Review, 2025)
This research addresses a key issue concerning the distinction between the contract subject and the obligation subject—whether they are separate concepts, interchangeable, or one replaces the other. The matter is complex, particularly as the Iraqi Civil Code refers to the contract subject inconsistently: sometimes as a core element of the contract, and other times as the obligation subject. This inconsistency has led to confusion, highlighting the need for a clear distinction between the two. The study aims to clarify this ambiguity, underscore the importance of differentiating the terms, and establish a standard to distinguish between them.